DESCRIPCIÓN E INTERPRETACIÓN EN LOS ARTÍCULOS SOBRE PINTURA DE GABRIEL FERRATER. - Malé-Pegueroles, Jordi (Revista Chilena de Literatura, 2025)
Gabriel Ferrater wrote several texts on art, mainly on painting, during the 1950s. Some were published in the Barcelona magazine Laye, others were part of a history of Spanish painting that was never published, and others are catalog texts or book reviews. Ferrater's ideal was to exercise scientific and objective art criticism. But to comment on works of art, he had to find a technical language to describe them, which contrasted with his poetic temperament. And although he was more interested in the form than in the content of the paintings, he also sometimes interpreted them. These ambivalent attitudes are the subject of this paper.